Affirming Multicultural Values in Contemporary Islamic Constitutional Law: A Study on the Principles of the Medina Charter - Nurhikma, Nurhikma; Rain, Titik Jauhar Firdha; Kurniati, Kurniati (Jurnal El-Thawalib, 2025)
The Medina Charter represents not only a historical foundation of early Islamic politics but also a relevant paradigm for addressing the challenges of multiculturalism in modern constitutional systems. This study examines the extent to which the principles embodied in the Charter, such as equality of citizens (al-musawah), justice (al-‘adalah), freedom of religion, minority protection, social solidarity, and consultation (shura), can serve as constitutional values to promote inclusive, democratic, and just governance in contemporary contexts. Employing a qualitative-descriptive approach with a normative-juridical analysis, this research examines classical Islamic political texts in conjunction with modern constitutional theories. The findings suggest that, if interpreted contextually and supported by institutional strengthening and constitutional reform, the Medina Charter can provide a constructive framework for establishing a pluralistic and democratic state. Furthermore, the integration of Islamic-based multicultural education is identified as a strategic means to foster collective awareness of peaceful coexistence in diverse societies. This study highlights that the Charter should not remain a static historical document, but instead be viewed as a living constitutional reference capable of inspiring the development of Islamic constitutional practices that promote justice, democracy, and harmony. The novelty of this research lies in its effort to connect early Islamic constitutional values with contemporary challenges of multicultural governance, offering new insights for the actualization of the Medina Charter in modern state systems.